Sexuality in Adults With ADHD: Results of an Online Survey - Hertz, Priscilla Gregório; Turner, Daniel; Barra, Steffen; Biedermann, Laura; Retz-Junginger, Petra; Schöttle, Daniel; Retz, Wolfgang (Frontiers in Psychiatry, 2022)
Establishing a secure sexual identity is a major developmental goal of an individual´s transition from childhood to adolescence and the years that follow. Attention deficit/hyperactivity disorder (ADHD) as a neurodevelopmental disorder defined by the core symptoms of inattention, hyperactivity, and impulsivity, but also with emotional dysregulation, oppositional behaviors, or disorganization appearing early in life, can affect several areas of an individual’s personal and social development, including sexual health. Yet, the scientific knowledge about the relationship between ADHD and sexual functioning is still scarce. Using an anonymous online survey, we compared different sexual behaviors including risky sexual behaviors, hypersexual behaviors, and sexual dysfunctions between 206 individuals with (n = 139) and without (n = 76) ADHD. Individuals with ADHD reported significantly more hypersexual behaviors than non-ADHD individuals, whereas no differences were found concerning risky sexual behaviors or sexual dysfunctions. In women with ADHD, hypersexual behaviors, sexual risk-taking as well as sexual dysfunctions were closely related to symptoms of emotional dysregulation, impulsivity, and oppositional symptoms. In men with ADHD, the associations between ADHD symptomatology and the sexuality-related measures were less clear, however, signs of emotional dysregulation seemed to be relevant as well. Since individuals with ADHD seem to be at an increased risk of some peculiarities in sexual behavior, sexuality-related issues should be routinely addressed during clinical consultations to provide more holistic treatment in order to enhance individual well-being and quality of life.